2017
DOI: 10.1007/s10578-017-0746-8
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Screen for Child Anxiety Related Emotional Disorders Revised (SCARED-R) Scale and Sub-Scales in Swedish Youth

Abstract: We evaluated the clinical utility of the Swedish SCARED-R in child- and adolescent psychiatric outpatients (n = 239) and validated it against Longitudinal Expert All Data (LEAD) DSM IV diagnoses based on the Children’s Schedule for Affective Disorders and Schizophrenia (KSADS) and subsequent clinical work-up and treatment outcome. The SCARED-R total score and subscales had acceptable sensitivity/specificity for child and parent reports for cut-offs based on Receiver Operating Characteristics (ROC) curves, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Effectiveness involves the following: CY-BOCS [ 38 ], primary outcome; Child Obsessive-Compulsive Impact Scale-Revised (COIS-R) [ 39 ]; and Family Accommodation Scale for OCD–Self-Rated Version (FAS-SR) [ 40 ]. Comorbidity/psychological well-being involves the following: Strengths and Difficulties Questionnaire (SDQ) [ 41 ]; Child Behavior Checklist (CBCL) [ 42 ]; Youth Self-Report Questionnaire (YSR) [ 42 ]; Screen for Child Anxiety-Related Emotional Disorders-Revised (SCARED-R) [ 43 , 44 ]; Mood and Feelings Questionnaire (MFQ) [ 45 ]; KINDL-R [ 46 ]; Children’s Global Assessment Scale (CGAS) [ 47 ]; and Clinical Global Impressions Scale-Severity/Improvement (CGI-S, CGI-I) [ 48 ]. Other study parameters include the following: study-specific treatment integrity forms completed by the therapist following each treatment session and the Trimbos/iMTA Questionnaire for Costs associated with Psychiatric Illness (TiC-P) [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Effectiveness involves the following: CY-BOCS [ 38 ], primary outcome; Child Obsessive-Compulsive Impact Scale-Revised (COIS-R) [ 39 ]; and Family Accommodation Scale for OCD–Self-Rated Version (FAS-SR) [ 40 ]. Comorbidity/psychological well-being involves the following: Strengths and Difficulties Questionnaire (SDQ) [ 41 ]; Child Behavior Checklist (CBCL) [ 42 ]; Youth Self-Report Questionnaire (YSR) [ 42 ]; Screen for Child Anxiety-Related Emotional Disorders-Revised (SCARED-R) [ 43 , 44 ]; Mood and Feelings Questionnaire (MFQ) [ 45 ]; KINDL-R [ 46 ]; Children’s Global Assessment Scale (CGAS) [ 47 ]; and Clinical Global Impressions Scale-Severity/Improvement (CGI-S, CGI-I) [ 48 ]. Other study parameters include the following: study-specific treatment integrity forms completed by the therapist following each treatment session and the Trimbos/iMTA Questionnaire for Costs associated with Psychiatric Illness (TiC-P) [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research investigating informant discrepancy as a function of child's sex have yielded mixed results. Several studies have found no significant differences in informant agreement between girls and boys [6,8,11,12], while others report moderate differences [7,10,13,14]. Ethnicity [8], socioeconomic status (SES [8,14]), parental psychopathology, and a variety of other family-related factors [7,9,14] have also been investigated as potential predictors of discrepancy, though this research has been sparser.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 The SCARED offers the opportunity for the parentreport measure to complement the self-report measure, however, most studies show low to moderate agreement between parent and child reported anxiety symptoms. 33 Unfortunately, ROC-analysis of SCARED parent report measures was limited by missing parent-report data, and the lack of statistical significance of the result did not allow for a direct comparison of diagnostic performances of SCARED parent and self-report measures in cSLE. Correlation (r ¼ 0.33) between parent and self-report SCARED measures suggested weak agreement between parent and child informants as seen in other studies of healthy children, 34 in which children have repeatedly been found to be more accurate informants of their anxiety than their parents.…”
Section: Screening Measure Cut-pointsmentioning
confidence: 99%